Environmental impacts of tourism: a study on the perceptions of residents and tourists in the Municipality of Paraty-RJ - Fandé, Morto Baiém; Pereira, Vania Filippi Goulart Carvalho (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The high growth of tourism since the 1950’s has been accompanied by various environmental impacts on tourist destinations. These impacts, which are often unnoticed or ignored for financial reasons can produce, among other effects, the decline of tourist flow. Coastal zones, one of the most sought after destinations for tourists due to the natural attractions thereof, are vulnerable to any kind of anthropogenic pressure. This study comparatively evaluated the perception by locals and tourists on environmental impacts caused by tourism in the Municipality of Paraty - RJ. For that purpose, a questionnaire was applied randomly to residents and tourists in this municipality analyzing natural envi- ronment, transformed environment and sociocultural environment. The results of the survey indicated that both locals and tourists realized, albeit in different degrees, damage to the environment caused by tourist activity in the receiving location. The residents themselves, who were more pessimistic in assessing the negative environmental impacts, are aware of their role in the environment. It became evident that there is need for improvements in tourism planning, adoption of measures, policies and coordinated actions between the public and private sectors that prioritize the environmental aspect, aiming at the conservation of the environment and sustainable tourism.